2018
DOI: 10.1007/s00268-018-4582-1
|View full text |Cite
|
Sign up to set email alerts
|

A Transverse Colectomy is as Safe as an Extended Right or Left Colectomy for Mid‐Transverse Colon Cancer

Abstract: Our study underlines the oncological safety of a transverse colectomy for mid-transverse colon cancer. Although TC tumors were associated with poorer histopathological features, survival rates were comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 30 publications
5
63
0
Order By: Relevance
“…Segmental colectomy for tumours of the distal transverse colon and splenic flexure was similarly defined as resection of a length of transverse colon and proximal descending colon with ligation of the supplying middle colic vessels at its origin and where required ligation of the left colic vessel[13,14]. Extended colectomy included both left and right extended colectomy[2,5,[10][11][12]14] and sub-total colectomy[13]. All studies were published between 2013 and 2020.Overall a total of 3395 patients were included in the final analysis.Enrolment of patients spanned over29 years (1989-2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Segmental colectomy for tumours of the distal transverse colon and splenic flexure was similarly defined as resection of a length of transverse colon and proximal descending colon with ligation of the supplying middle colic vessels at its origin and where required ligation of the left colic vessel[13,14]. Extended colectomy included both left and right extended colectomy[2,5,[10][11][12]14] and sub-total colectomy[13]. All studies were published between 2013 and 2020.Overall a total of 3395 patients were included in the final analysis.Enrolment of patients spanned over29 years (1989-2018).…”
mentioning
confidence: 99%
“…There was no difference in disease-free survival with segmental compared to extended colectomy (OR 0.88, 95% CI 0.59-1.34, P = 0.56)(Figure 3b). The median follow-up ranged from 37 to 60 months(Table 1)[5,[10][11][12][13][14].Seven studies including 2584 patients reported comparative datafor all-cause mortality on long-term follow-up[2,5,[10][11][12][13][14]. There was no difference in overall survival between the segmental and extended colectomy groups (OR 0.98, 95% CI 0.68-1.4, P = 0.9;…”
mentioning
confidence: 99%
“…This means that D2 LFN versus D3 LFN in Japanese classification does not have any difference in DFS and OS ( Figure 4). For more results, it is necessary defining traverse colon tumor as a tumor of mid-transverse colon or on the right or left splenic flexure too and prospective trials with inclusion and exclusion criteria are needed to have clear oncological results and post-operative complications [2].…”
Section: Discussionmentioning
confidence: 99%
“…For TNM noticed that OS and DSF were similar between the two groups but there were fewer lymph nodes harvested and worse short-outcomes in TC group. TC group was also correlated with poor histopathological features and disease recurrence [2]. van Rongen et al have identified 103 patients, 34 TC/69 EC derived from the database stages I-II, 5-year survival was slightly higher for the hemicolectomy group (65% vs. 55%) but this difference did not reach statistical significance (p = 0.38, hazard ratio 1.4, 95% CI 0.6-3.1).…”
mentioning
confidence: 99%
“…However, subgroup analysis revealed that for the larger tumors (>5 cm), there was a survival advantage following extended colectomy Leijssen et al 14 around one-third of the procedures were performed by laparoscopic approach. These two studies also noted an increasing trend of laparoscopic surgery and decreasing numbers of transverse colectomy in the latter half of the study period.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%